2013
DOI: 10.1002/wsb.349
|View full text |Cite
|
Sign up to set email alerts
|

Detecting short-term responses to weekend recreation activity: Desert bighorn sheep avoidance of hiking trails

Abstract: To study potential effects of recreation activity on habitat use of desert bighorn sheep (Ovis canadensis nelsoni), we placed Global Positioning System collars on 10 female bighorn sheep within the Wonderland of Rocks–Queen Mountain region of Joshua Tree National Park (JOTR), California, USA, from 2002 to 2004. Recreation use was highest from March to April and during weekends throughout the year. Daily use of recreation trails was highest during midday. By comparing habitat use (slope, ruggedness, distance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Understanding the behavioral response of wildlife to people is an information gap with critical conservation and management implications (Buchholz 2007, Caro 2007, Blumstein and Fernandez-Juricic 2010. Previous studies have shown that large mammals can adjust their location and timing of certain behaviors to avoid interacting with people, including hikers (Rogala et al 2011, Longshore et al 2013, skiers (Ferguson andKeith 1982, Cassirer et al 1992), aircraft (Weisenberger et al 1996, Krausman et al 1998) and vehicles (Burson et al 2000, Brown et al 2012. Some of these behaviors generate cascading effects on other human-wildlife interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the behavioral response of wildlife to people is an information gap with critical conservation and management implications (Buchholz 2007, Caro 2007, Blumstein and Fernandez-Juricic 2010. Previous studies have shown that large mammals can adjust their location and timing of certain behaviors to avoid interacting with people, including hikers (Rogala et al 2011, Longshore et al 2013, skiers (Ferguson andKeith 1982, Cassirer et al 1992), aircraft (Weisenberger et al 1996, Krausman et al 1998) and vehicles (Burson et al 2000, Brown et al 2012. Some of these behaviors generate cascading effects on other human-wildlife interactions.…”
Section: Discussionmentioning
confidence: 99%
“…; McLellan and Shackleton 1988, Gibeau et al 2002, Moen et al 2012) and bighorn sheep (Ovis sp. ; Longshore et al 2013). At the same time, wildlife can become habituated to such disturbances and adjust their behavior to minimize encounters with people (Schultz and Bailey 1978, Burson et al 2000, Brown et al 2012; perhaps with little consequence to the demographic vital rates of wildlife populations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Canada lynx were neutral or exhibited a slight proclivity to use roaded areas similar to lynx populations in the northern Rockies (Squires et al 2010). In contrast to bighorn sheep (Ovis canadensis nelson) that adjusted space-use near high-use recreation trails (Longshore and Thompson 2013), Canada lynx also exhibited little behavioral response to backcountry ski trails as evidenced by their increased probability of use near (<250 m) trails and no diel pattern in their association with trails despite varying levels of human disturbance during day (high disturbance) vs. night (no disturbance, Olson et al 2018). Thus, we believe the proclivity of Canada lynx to associate with roads and trails was due to their patterns of resource selection in forested landscapes with associated road and trail infrastructures rather than responding to human activity present along these linear structures.…”
Section: Discussionmentioning
confidence: 98%
“…). In contrast to bighorn sheep ( Ovis canadensis nelson ) that adjusted space‐use near high‐use recreation trails (Longshore and Thompson ), Canada lynx also exhibited little behavioral response to backcountry ski trails as evidenced by their increased probability of use near (<250 m) trails and no diel pattern in their association with trails despite varying levels of human disturbance during day (high disturbance) vs. night (no disturbance, Olson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Although such studies are expensive and difficult to implement (Beale ), effects of disturbance or cumulative perturbations have implications for the fitness of individuals (Ciuti et al ), with resultant population‐level consequences (Stockwell et al , Bleich et al , Côté ). For example, animals with habitat of similar quality nearby may be able to avoid disturbances because they have alternate sites to occupy (Longshore et al ), but such is not always the case. Indeed, if animals abandon habitat in response to disturbance and move to areas that are less suitable in terms of forage or cover, it is likely that individual fitness will suffer, which could translate into population‐level impacts.…”
mentioning
confidence: 99%